2021
DOI: 10.1055/s-0041-1731343
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Streptococcus pneumoniae Nasopharyngeal Carriage and Antimicrobial Susceptibility among Children Under the Age of 5 Years in the Southwestern Colombia

Abstract: Objective This work aims to evaluate the factors associated with Streptococcus pneumoniae nasopharyngeal colonization and antimicrobial susceptibility among pediatric outpatients in southwestern Colombia, 2019. Methods A cross-sectional study was performed using survey-based interviews and the collection of nasopharyngeal-swab specimens for microbiological characterization and antimicrobial susceptibility testing. Logistic regression analyses were performed for factors associated with nasopharyngeal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Additionally, a 2019 study to determine the rate of nasopharyngeal carriage in children under 5 years of age, conducted in Cali, reported high rates of resistance. Decreased sensitivity to penicillin (57%), ceftriaxone (21%), erythromycin (40%), trimethoprimsulfamethoxazole (36%), and clindamycin (24%) was detected, evidencing the importance of colonization as a reservoir of multi-resistant isolates with an impact on transmission and subsequent IPDs in this population 50 . Finally, data from the Pneumo-Colombia Network have shown that serotypes 19A, 6A, 14, 23F and 6C are the ones that exhibit a higher resistance pattern.…”
Section: Considerations On the Evolution Of The Antimicrobial Suscept...mentioning
confidence: 95%
“…Additionally, a 2019 study to determine the rate of nasopharyngeal carriage in children under 5 years of age, conducted in Cali, reported high rates of resistance. Decreased sensitivity to penicillin (57%), ceftriaxone (21%), erythromycin (40%), trimethoprimsulfamethoxazole (36%), and clindamycin (24%) was detected, evidencing the importance of colonization as a reservoir of multi-resistant isolates with an impact on transmission and subsequent IPDs in this population 50 . Finally, data from the Pneumo-Colombia Network have shown that serotypes 19A, 6A, 14, 23F and 6C are the ones that exhibit a higher resistance pattern.…”
Section: Considerations On the Evolution Of The Antimicrobial Suscept...mentioning
confidence: 95%
“…Previous studies reported the attendance at day care as a main factor causing the increase of the carriage rate of S. pneumoniae [25]. However, higher pneumococcal carriage frequencies were observed among participants aged <2 years, and in individuals belonging to indigenous communities lacking established pneumococcal-conjugated vaccine immunization schemes, as found in Southwestern Columbia [26]. The distribution and prevalence of the pneumococcal serotypes and carriage varies geographically, therefore it is essential to perform pneumococcal prevalence studies in different geographical areas [27].…”
Section: Discussionmentioning
confidence: 88%
“…Otitis-prone children have underlying dysfunctions in immune defense mechanisms, including innate immunity (e.g., inadequate response of proinflammatory cytokines and poor repair of epithelial cells in the nasopharynx) and adaptive immunity (e.g., dysfunction of B cells and immunologic memory with low antibody production to otopathogen-specific antigens as well as dysfunction of CD4 þ and CD8 þ T cells). 3,21,22 Besides these minor immunological aberrations, a small but important subset of children with rAOM has well-defined IEIs. 7 The present study identified a relatively high frequency of IEIs in children with rAOM (one of every five children).…”
Section: Discussionmentioning
confidence: 99%